Gestión empresarial y competitividad de empresas de supervisión y análisis químico al sector minero del Perú, año 2022 - Cárdenas Mariluz, Diego Hilario (2025)
This research aims to determine the relationship between business management and competitiveness of a group of companies that provided supervision and chemical analysis services to the mining sector in Peru in 2022. The methodology consisted of the quantitative approach, the basic type research, the non-experimental, cross-sectional correlational design, and the hypothetico-deductive and inductive method were used. The survey technique and the Likert scale were used as instruments. The simple random probabilistic sample consisted of 70 participants, who are employees of mining companies that received the outsourcing service in supervision and chemical analysis to the mining sector in Peru.The results showed that, at a significance level of 0.05, a p-value = 0.000 and a Spearman’s rho correlation = 0.841 were obtained, which allowed affirming the alternative hypothesis and concluding that business management was directly and significantly related to competitiveness in a group of companies that provided chemical analysis and supervision services to Peruvian mining sector in 2022.